ANALISIS KREDIT BERMASALAH PADA PT BANK WOORI SAUDARA INDONESIA 1906 TBK - Wahyu, Didin Rasyiddin; Hasanah, Siti Maulidah (LP2M Universitas Bina Bangsa, 2024)
Credit quality determination refers to Bank Indonesia regulations, namely PBI No.14/15/PBI/2012 concerning Asset Quality Assessment of Commercial Banks. For non-performing loans that arise, immediate handling is needed by the bank so that it is not sustainable into bad loans and affects the bank's health level The purpose of this study is to analyze the development of non-performing loans, find out the causes of non-performing loans and find out how to handle non-performing loans at PT Bank Woori Saudara Indonesia 1906 Tbk The method used in this study is descriptive qualitative method. While the data collection techniques carried out are literature study techniques or secondary data and non-statistical quantitative data analysis techniques using Net Performing Loan financial ratios The results of this study state that the average NPL for 5 years starting from 2018-2022 is 1.821% in accordance with Bank Indonesia (BI) regulation No. 15/2/PBI/2013 if ≤ 5%, then the company's health level is at a healthy predicate The discussion of this research is the analysis of non-performing loans at PT Bank Woori Saudara Indonesia 1906 Tbk for the 2018-2022 period, the causes of non-performing loans and how to handle non-performing loans The conclusion of this study is that the average NPL 2018-2022 of 1.821% or ≤ 5% is in a healthy predicate, the causes of non-performing loans are caused by the Covid-19 pandemic, internal bank factors and debtor ineligibility while the way to handle it is the Covid-19 pandemic relaxation policy, rescheduling, reconditioning and restructuring